A “DOSPEMKU” CHAT APPLICATION PROTOTYPE WITH THREADING FEATURE USING CORDOVA FRAMEWORK FOR ANDROID-BASED COMPETENCY CONSULTATION: Chat Application With Threading Feature Using Cordova Framework For Android-Based - Anwar Ibrahin Dana; Ahmad Zuhdi; Gatot Budi Santoso (Intelmatics, 2023)
Abstract—In this days, human communication that is efficient and easy is through a system of social media chat application devices. By relying on internet signals, users can carry out meeting activities between one party using social media without the need to use face-to-face meetings, one of which is in communicating consultations on competency issues in the world of education. The reference for this final project is based on the author's thoughts to form a web-based media Halodoc, which is the formulation of the core problem of this final project. With DOSPEMKU, the author can hope to solve some case examples. As for examples of cases such as difficulties coming because there is no time to go (in busyness), determining a time schedule that is not suitable, being inflexible, and so on. DOSPEMKU is a chat application based on the Android operating system, implementing Usecase Diagrams and Activity Diagrams as a designer for functionality requirements that are implemented into DOSPEMKU. The Cordova network is used as an Integrated Development Environment (IDE) platform with html, javascript programming languages ​​and uses the phpMyAdmin database as the database base. Design Implementation uses several methods, ranging from interface design, database, to functionality design in determining what features are contained in DOSPEMKU. The implementation process is tested both in terms of functionality and non-functionality to test whether the application is in accordance with the design stage. So that the process of designing, implementing and testing it was found that the application was made according to and accommodated the conversation according to the discussion.